Neighborhood-level social vulnerability and individual-level cognitive and motor functioning over time in older non-Latino Black and Latino adults - Lamar, Melissa; Kershaw, Kiarri N.; Leurgans, Sue E.; Mukherjee, R. Reshmi; Lange-Maia, Brittney S.; Marquez, David X.; Barnes, Lisa L. (Frontiers in Human Neuroscience, 2023)
Abstract Introduction: Despite known health disparities in cognitive aging, a comprehensive rationale for the increased burden in older minoritized populations including non-Latino Black and Latino adults has yet to be elucidated. While most work has focused on person-specific risk, studies are increasingly assessing neighborhood-level risk. We evaluated multiple aspects of the environmental milieu that may be critical when considering vulnerability to adverse health outcomes. Methods: We investigated associations between a Census-tract derived Social Vulnerability Index (SVI) and level of and change in cognitive and motor functioning in 780 older adults (590 non-Latino Black adults, ~73 years old at baseline; 190 Latinos, ~70 years old baseline). Total SVI scores (higher=greater neighborhood-level vulnerability) were combined with annual evaluations of cognitive and motor functioning (follow-up ranged from 2 to 18 years). Demographically-adjusted mixed linear regression models tested for associations between SVI and cognitive and motor outcomes in analyses stratified by ethno-racial group. Results: For non-Latino Black participants, higher SVI scores were associated with lower levels of global cognitive and motor functioning – specifically, episodic memory, motor dexterity and gait – as well as longitudinal change in visuospatial abilities and hand strength. For Latinos, higher SVI scores were associated with lower levels of global motor functioning only – specifically, motor dexterity; there were no significant associations between SVI and change in motor functioning. Discussion: Neighborhood-level social vulnerability is associated with cognitive and motor functioning in non-Latino Black and Latino older adults, although associations appear to contribute to level more so than longitudinal change.